SEMANTIC ANALYSIS: LEXICAL RELATIONS IN KATY PERRY'S SONG LYRICS - Selvira A. R. Talohanas; Rawuh Yuda Yuwana (Acceleration: Multidisciplinary Research Journal, 2023)
Song or singing is a literary product or work of art that connects sound art and language art to become sound art which involves the melody and vocal color of the singer. This study aims to classify the types of lexical relations in Katy Perry's song lyrics and then describe their meaning according to the context of the song lyrics. Saeed's theory is used in this study as a reference for analyzing data. Based on the research results, found Homonymy, Polysemy, Synonymy, Antonymy, Hyponymy, and Meronymy in song lyrics (1) Firework (2) Roar (3) Wide Awake (4) Hot N Cold (5) Teenage Dream (6) Part of Me ( 7) Dark Horse (8) Unconditionally.